2009
DOI: 10.1124/mol.109.056085
|View full text |Cite
|
Sign up to set email alerts
|

Apratoxin A Reversibly Inhibits the Secretory Pathway by Preventing Cotranslational Translocation

Abstract: Apratoxin A is a potent cytotoxic marine natural product that rapidly inhibits signal transducer and activator of transcription (STAT) 3 phosphorylation by an undefined mechanism. We have used biochemical and proteomics approaches to illuminate upstream molecular events. Apratoxin A inhibits Janus kinase (JAK)/STAT signaling through rapid down-regulation of interleukin 6 signal transducer (gp130). Apratoxin A also depletes cancer cells of several cancer-associated receptor tyrosine kinases by preventing their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
108
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(114 citation statements)
references
References 42 publications
6
108
0
Order By: Relevance
“…The Sec61 complex is also responsible for export of mis-folded proteins from the ER lumen to the cytosol for further degradation (27). It has been demonstrated previously that apratoxin A can block cotranslational translocation (9). Downregulation of several membrane-associated receptors, such as gp130, c-MET, HER-2, PDGFR-b, and IGF1R-b, was also reported following apratoxin A exposure.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The Sec61 complex is also responsible for export of mis-folded proteins from the ER lumen to the cytosol for further degradation (27). It has been demonstrated previously that apratoxin A can block cotranslational translocation (9). Downregulation of several membrane-associated receptors, such as gp130, c-MET, HER-2, PDGFR-b, and IGF1R-b, was also reported following apratoxin A exposure.…”
Section: Discussionmentioning
confidence: 91%
“…It has also been suggested that apratoxin A can stabilize Hsc70/Hsp70 interaction with Hsp90 client proteins to prevent their binding to Hsp90; such stabilization results in degradation of EGFR and ErbB2 through chaperone-mediated autophagy (8). In a cell-free in vitro system, apratoxin A was also shown to inhibit the secretory pathway by preventing cotranslational translocation of newly synthesized proteins (9).…”
Section: Introductionmentioning
confidence: 97%
“…Most of these inhibitors interfere with a specific step in the translocation process and thus affect a wide spectrum of translocon substrates, often associated with cellular toxicity (35,36). The fungal cyclic heptadepsipeptide HUN-7293 was originally identified as an inhibitor of vascular cell adhesion molecule 1 (VCAM-1) expression in endothelial cells (37,38).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the accumulation of cytosolic proteins that would result from an inhibition of ER translocation might also contribute to the cytotoxicity of ES I and its potential anticancer properties (Rane et al, 2008;Wang et al, 2009). The inhibition of ER translocation by the cyclodepsipeptide apratoxinA has also been linked to an anticancer effect, in this case by preventing the biosynthesis of cancer-associated receptor tyrosine kinases (Liu et al, 2009). Thus, modulation of protein homeostasis by targeting fundamental cellular components such as the Sec61 complex appears to be a valid target for therapeutic intervention.…”
Section: Discussionmentioning
confidence: 99%